The Influence of Nitrogen Application Level on Eating Quality of the Two Indica-Japonica Hybrid Rice Cultivars - Xincheng Zhang; Liangbo Fu; Yishan Tu; Huifang Zhao; Liuhui Kuang; Guoping Zhang (Plants, 2020)
Indica-japonica hybrid rice cultivars show great yield potential but poor eating quality and require more nitrogen (N) input relative to japonica rice. However, the effect of N levels on the eating quality of indica-japonica hybrid rice is little known. A field experiment was carried out to investigate the effects of four N levels on two indica-japonica hybrid rice cultivars (Yongyou12 and Yongyou17) differing in eating quality. The results showed that the contents of amylose chains and water-insoluble storage proteins, especially prolamin, increased largely under a high N level, leading to deterioration of the rice-eating quality, although a low N level (100 N kg/ha) had a less negative effect on the eating quality. Moreover, both of the indica-japonica hybrids had high ratios of inferior grains (IG), and the ratio of IG increased with the N level. Grain weight and the immature ratio of IG were reduced and increased with the N level, respectively, which are also factors for deterioration of the eating quality. The two cultivars differed greatly in the responses of eating quality to the N level, with Yongyou17 being more sensitive than Yongyou12. The current results indicated that a high N level deteriorates the eating quality of indica-japonica hybrid rice mainly due to a large increase of IG.